All-trans retinoic acid regulated prohibitin by retinoic acid receptor Î± in hypoxia-induced renal tubular epithelial cell injury - Zhou, Tianbiao; Li, Hong-Yan; Zhong, Hongzhen; Zhong, Zhiqing (Cellular and Molecular Biology, 2019)
All-trans retinoic acid (ATRA) is a critical component in cell processes such as cell growth, differentiation and apoptosis, and it is also crucial in the regulation of extracellular matrix (ECM) deposition. Prohibitin (PHB) can regulate cell proliferation, apoptosis and differentiation. The current study investigated whether ATRA regulated PHB is induced by hypoxia/reoxygenation injury in renal tubular epithelial cells (RTEC), using gene interference treatments (knockdown or overexpression of RARÎ±). Our results indicate that ATRA can augment the expression of RARÎ± and PHB proteins and reduce the expression of TGF-Î²1, FN and Col-IV proteins. PHB expression was reduced in an ATRA treated RARÎ±- group, and TGF-Î²1, FN and Col-IV were up-regulated compared to the ATRA treated RARÎ±+ group. We postulate that ATRA can induce the PHB expression by RARÎ± in hypoxia/reperfusion related RTEC injury.